Let a and b be any two real numbers. Consider the number x defined by
x = ab + (-a)(b) + (-a)(-b).
We can write
x = ab + (-a)[ (b) + (-b) ] (factor out -a)
= ab + (-a)(0)
= ab + 0
= ab.
Also,
x = [ a + (-a) ]b + (-a)(-b) (factor out b)
= 0 * b + (-a)(-b)
= 0 + (-a)(-b)
= (-a)(-b).
So we have
x = ab
and
x = (-a)(-b)
Hence, by the transitivity of equality, we have
ab = (-a)(-b).
2006-11-08 14:26:20
·
answer #1
·
answered by Clueless 4
·
1⤊
0⤋
Hmm... OK, let a and b be any two positive numbers and n = -b.
Then, trivially ab - ab = 0. Also, -ab = an, so ab + an = 0. Since we know ab is positive, then an must be negative. Therefore, the product of a positive number and a negative number must be negative.
Now let a and b be any two negative numbers and n = -b. (Note that n is positive.)
Again, ab - ab = 0 and -ab = an, so ab + an = 0. Since we know from the previous logic that an must be negative, it follows that ab must be positive. Therefore, the product of two negative numbers must be positive.
2006-11-08 14:05:16
·
answer #2
·
answered by Anonymous
·
0⤊
0⤋
When both factors are negative, as in -4(-5), the sign of the product is positive. We are to take away -5 four times.
-4(-5) = -(-5) - (-5) -(-5) -(-5) becomes +5 +5 +5 +5
Of course, +5+5+5+5 = 20.
Remember that taking away a negative 5 is the same as adding a positive 5.
Guido
2006-11-08 14:04:45
·
answer #3
·
answered by Anonymous
·
0⤊
0⤋
This is gonna sound really stupid...but a professor once told me that two negative people will have a positive relationship and that it's the same way with numbers....It helped me remember...Hope it helps you too!! :)
2006-11-08 13:45:55
·
answer #4
·
answered by Jovigrl 2
·
0⤊
0⤋
Well, it's common sense. A negetive number times a negetive number will always give you a positive number. Just think of peanut butter and jelly; peanut butter is way different than jelly, if you combine them together, you get a postive result :D
2006-11-08 13:54:37
·
answer #5
·
answered by Anonymous
·
0⤊
1⤋
Let a and b be positive real numbers, so that
-a < 0 and -b <0. [Need to show (-a)(-b) > 0]
now, (-a)(-b) = (-1)(a)(-1)(b) = (-1)(-1)(a)(b) = (1)(a)(b)
= 1 (ab) = (ab) = ab > 0.
so, (-a)(-b) = ab = c >0 (c = ab, another real number). QED
2006-11-08 21:50:27
·
answer #6
·
answered by mr green 4
·
0⤊
0⤋
The same concept with sentence construction!
You cannot "double negative in a sentence".
Example: He is not unworthy of the prize.
"Not" and "unworthy" is both negative so it yealds a positive structure!!! So thats how you handle it!!!
Good luck!!!!
2006-11-08 13:45:37
·
answer #7
·
answered by bugi 6
·
1⤊
0⤋
it is a regulation, or convention, in arithmetic. you could, although, be sure that the manufactured from 2 destructive numbers is a superb quantity: you could in elementary terms divide an excellent quantity with a destructive quantity to derive a destructive quantity.
2016-12-14 04:01:56
·
answer #8
·
answered by endicott 4
·
0⤊
0⤋